Development of a Diabetes Mellitus Monitoring Information System in Health Monitoring and Health Decision Making - Renata, Agnes Lia; Fatmasari, Diyah; Sukini, Sukini (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
Individuals with diabetes mellitus are more likely to experience acute and chronic health complications including oral diseases. However, there are still many of them who do not carry out routine controls and do not record the history of examination results, resulting in a lack of monitoring of their health. Information systems in the health sector can be utilized in managing health information as an effort to monitor risk factors that allow complications of oral and dental disease. In addition, there is no information system that focuses on monitoring dental health in patients with diabetes mellitus. The development of SIP DM-DENT Monitoring is focused on monitoring general health and dental health in patients with diabetes mellitus. This study aims to produce SIP DM-DENT Monitoring for people with diabetes mellitus that is feasible in monitoring health and providing health recommendations based on the results of their health checks, especially in controlling blood sugar and dental health. This research combines descriptive and analytical types of research called R&D to develop a new product output with the stages of information gathering, design making, expert validation, product testing and product results. The data collected is primary data using interview questionnaires and Linkert questionnaires. Sampling using purposive sampling technique obtained a sample of 35 respondents. The data obtained were analyzed using ICC test and descriptive statistics. The average result of the expert validation assessment was 85.76 with a decent category. The ICC test results show a p-value of 0.00 <0.05 which means the system is feasible to use. While in the product test assessment, the average respondent agrees that the system provides information and is easy to use. Based on this research, it shows that SIP DM-DENT Monitoring is feasible and effective in monitoring the health of people with diabetes mellitus and providing health recommendations for them.